A Comprehensive Study of Route Prediction Algorithms - Singh, Dimple; Pritam; Duhan, Neelam; Bhatia, Komal Kumar (International Journal of Computer Sciences and Engineering, 2019)
The position of an individual on Earth is of great importance and can have enormous applications such as Route Recommendation, Driving Navigation, Vehicular Turn Prediction, Travel Pattern Similarity, Pattern Mining, Route Planning, Social Networks, Vehicular ad-hoc networks and so on. Trying to figure out where you are and where you are going is probably one of man’s oldest pastimes. Route Prediction is also dealing with the same thing. There are many attributes, for example, temporal attributes, and transportation means, which can also be used for predicting next optimal point towards the destination. Over the years, all kinds of technologies have tried to simplify this task such as Landmark Techniques, Dead Reckoning Technique, Celestial Techniques, OMEGA Technique, LORAN Techniques, Satellite Navigation Technique and so on. This paper gives a detailed survey of some recent algorithms of route prediction, the attributes handled by them and the methods used by them.